ANALISIS POROSITAS DAN SATURASI AIR DALAM INTEGRASI PETROPHYSICS DAN SEISMIC MULTIATTRIBUTES UNTUK KARAKTERISASI RESERVOIR - Gian Antariksa; Hernowo Danusaputro; Tony Yulianto (Youngster Physics Journal, 2016)
Plan of Development I is the development plan of one or more oil and gas fields in an integrated way (integrated) to develop and produce hydrocarbon reserves. Field development was conducted in order to know the area indications of hydrocarbons based on petrophysics analysis and determine its content with multiattributes. By integrating the study of seismic data, well data (including petrophysical analysis) with geological and stratigraphic information is a necessary step to determine the characteristics of a reservoir. Formation evaluation and petrophysical analysis as an initial stage to characterize the reservoir by studying rock properties such as volume of clay, porosity and water saturation. Multiattribut seismic analysis is used to predict the physical properties of the rock as a whole in the seismic volume. Based on the results of the petrophysical analysis of the target porosity ranges from 11% -14%, from the netpay statistical data lumping results have value Net to Gross range of 7% to 40%.and water saturation ranging from 18% -38%. Seismic multiatributtes method can predict petrophysical analyzes well in the target zone.